DEVELOPMENT OF INTERACTIVE MULTIMEDIA USING THE MACROMEDIA FLASH AND SCIENCE APPROACH FOR ENGINEERING MATERIALS COURSES IN MECHANICAL ENGINEERING EDUCATION UNIVERSITAS SRIWIJAYA - Imam Syofii; Rukiyah Rukiyah; Dewi Puspita Sari (Universitas Sriwijaya, 2020)
This study aims to developing interactive multimedia using Macromedia Flash and science approach for Engineering Materials courses in study program of Mechanical Engineering Education, Universitas Sriwijaya. The Macromedia flash was used because run easily on a computer or laptop without supporting applications (user friendly). While science approach was used because Engineering Material course are science based. The development of interactive multimedia was used the Rowntree method. The Rowntree method has three stage: planning; development and evaluation. Based on results, interactive multimedia using Macromedia flash and science approach are valid with percentage of 83% for multimedia and 75.58% for matters, practice with percentage in small group test of 86%, and effective with percentage in field test of 100%. Thus, the interactive multimedia that has been developed is recommended for use in study program of Mechanical Engineering Education, Universitas Sriwijaya.